RISK ANALYSIS OF MUDHARABAH AND WADIAH CONTRACTS IN THE MANAGEMENT OF HAJJ FUNDS AT BANK SYARIAH INDONESIA - Achmad Junaidi; Khaled Marzuki; Putri Salsabila (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2026)
Fundraising remains the primary pillar of stability in Islamic banking, with Hajj funds serving as a strategic long term funding source for Bank Syariah Indonesia (BSI). However, the management of these large scale funds involves complex risk dynamics influenced by macroeconomic fluctuations and the rising competitiveness of the Islamic capital market. This study aims to analyze risk management within Mudharabah and Wadiah contracts in the context of Hajj fund management during the post-merger BSI era leading toward 2026. Employing a qualitative descriptive approach with a Systematic Literature Review (SLR) method, this research synthesizes findings from 21 reputable journal articles published between 2019 and 2026, screened via the PRISMA protocol. The results indicate that Mudharabah contracts exhibit high vulnerability to Displaced Commercial Risk (DCR) due to the volatility of bank income and financing quality (NPF), while Wadiah contracts require stringent mitigation of Systemic Liquidity Risk to ensure fund availability during potential